THE DIFFERENCE OF PAIN SCALE USING NUMERIC RATING SCALE AND VISUAL ANALOG SCALE IN POST-OPERATIVE PATIENTS - Natya Ayu Paluwih; Riama Marlyn Sihombing; Kinanthi Lebdawicaksaputri (Universitas Pelita Harapan, 2019)
Post-operative pain is acute and subjective therefore the perceived pain intensity will be different. In one of the western Indonesia Hospitals in measuring the pain threshold using 2 tools namely Numeric Rating Scale and Wong Baker Face. Measurement of the pain intensity can be done with NRS and VAS scale. The objective of this research was to identify the difference of pain scale using the NRS and VAS scale in post-operative patients. The research method was descriptive quantitative using comparative approach. The study was conducted on 1 November 2017 – 12 December 2017.The population of the study are the post-operative patients at the In-Patient wards in a private hospital in Western Part of Indonesia. The samples were obtained using purposive sampling with n = 41. Research instrument consists of observation sheet using NRS and VAS scale. The results showed most respondents during the first eight hours using NRS scale had mild pain (80.5%); first 16 hours had light pain (63.4%); and had mild pain in the first 24 hours (85.4%). Using VAS scale, most of the respondents on the first eight hours has mild pain (87.8%); first 16 hours has mild pain (68.3%); and has mild pain in the first 24 hours (87.8%). The conclusion of this study is there is no difference in pain scale of post-operative patients using VAS scale and NRS scale. So, hospitals can also use the VAS scale to assess pain scale in post-operative patients.